Hästägares kunskapsnivå och attityder angående hästutfodring - Gröndahl, Andrea (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
Horse owner’s knowledge about horse feeding and nutrition is directly linked to the horse’s health and welfare. According to several studies, both Swedish and foreign, horse owners generally have inadequate knowledge about horse feeding. The housing systems and feeding routines of today differs in many ways from what horses have adapted to through evolution. Wild horses live in harem herds and roam on large open fields, spending about 60 % of the day grazing, mainly grass and herbs. Horses are thereby adapted to a diet high on fibers and low on starch. Horses today are being housed individually through large parts of the day and fed restricted amounts of roughage, which can reduce the feeding time significantly. The roughage is often supplemented with cereal-based foods rich on starch.